"Never Again War". Issue 1 (March 2014) - Norris, Kristopher
Abstract This essay addresses the complexities of the Roman Catholic position on war by evaluating recent documentary evidence, attending to the contemporary challenges of terrorism and humanitarian interventions. It presents two arguments. First, attending to traditional Catholic resources for assessing war, papal criticism of recent military action, and debates about a recent shift in Catholic just war logic, this essay argues that Catholic teaching on war has undergone a repositioning in a pacifist direction. Second, it contends that recent critiques of this shift in position by scholars such as George Weigel and James Turner Johnson, however, are wrong to categorize this a "functional pacifism." Though a development from within just war theory and pacifist reasoning, the Church's new stance does not operate as a type of pacifism, allowing too many possibilities for justified armed conflict to be labeled as "functional" pacifism. The essay concludes by examining the traditional Catholic theological commitments that place limits on any movement toward pacifism, precluding even a functionally pacifist position.